How Close to the “Honeypot?”: A Comparative Analysis of Cannabis Markets Under Two Different Policies Toward Personal Cultivation - Belackova, Vendula (International criminal justice review, 2018)
Background:This study aimed to assess how cannabis markets compare in two states with different cannabis policies. The possession of cannabis is decriminalized in both the Czech Republic (de facto) and in New South Wales (NSW; de jure), but personal cannabis cultivation has been tolerated/decriminalized only in the Czech Republic.Methods:Semistructured interviews were conducted in the Czech Republic (n = 25) and in NSW, Australia (n = 25) between 2009 and 2014 and analyzed with thematic and qualitative content analysis.Findings:The Czech respondents often grew their own cannabis or got it directly from somebody who grew it. Cannabis users in both places preferred quality cannabis which was free of chemicals, but the Australian respondents seemed more likely to get cannabis that varied in quality and was potentially produced under large-scale, unsafe conditions. Triangulation with other data sources suggests that these findings could apply more broadly.Conclusions:The findings of this study indicate that policy can encourage the proliferation of small-scale cannabis cultivation, leading to lower health and social risks. Policy approaches that tolerate such cultivation should be considered as an alternative or as a complement to the existing or proposed cannabis policies.